MORAL EDUCATION IN SEMAR CHARACTER REVIEWED FROM A SOCIOLOGICAL ASPECT - Soimah Lailah; Ghufron Hamzah; Dinda Helmi Kayana Juwita (Taskuliah Edukasi Indonesia, 2025)
This research aims to explore the moral education contained in the Javanese shadow puppet performance art of the character Semar, with a focus on the socialization aspect. The character Semar is a figure with rich moral values in Javanese culture and has a significant impact on the formation of people's character. This research uses the library research method, namely text analysis, observation, and interviews with Javanese performers and community leaders to identify the social values contained in the character of Semar. The research results show that from Karl Mannheim's sociological perspective, the meaning of sociological events is divided into three acts of meaning, namely objective, expressive and documentary. From the objective meaning, Semar's character plays a role in conveying moral messages, such as wisdom, simplicity and a sense of humor, and also teaches the importance of empathy and mutual respect in Javanese society. From the expressive meaning, Semar's character is depicted with distinctive features with a round and cute face as a source of entertainment and laughter in wayang performances. From the meaning of the documentary, it describes local wisdom and Javanese traditions. Moral education through the character Semar influences viewers, especially children, to internalize these moral values in life. In conclusion, the character of Semar in Javanese shadow puppet performances has a crucial role in moral education and social character formation in Javanese society. This research provides valuable insight into how traditional performing arts can be a means of moral and cultural education in society.